2017
DOI: 10.1016/j.physletb.2017.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Next-to-leading-order QCD corrections to e + e − → H + γ

Abstract: Within the nonrelativistic QCD (NRQCD) factorization framework, we have computed the O(α 2 s) corrections to the exclusive production of P-wave spin-triplet charmonia χ cJ (J = 0, 1, 2) accompanied with a hard photon at B factory. For the first time, we have explicitly verified the validity of NRQCD factorization for exclusive Pwave quarkonium production to two-loop order. Unlike the χ cJ electromagnetic decays, the O(α 2 s) corrections are found to be smaller than the O(α s) corrections in all three channels … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 84 publications
2
11
0
Order By: Relevance
“…For the ITM we newly implemented the relevant pieces, based on the IDM. We validated our numerical calculations by comparing with the earlier works in the SM [7,9] as well as in the IDM [19], while the results in the ITM and the THDMs are reported for the first time in this article.…”
Section: Two Higgs Doublet Modelsmentioning
confidence: 61%
See 3 more Smart Citations
“…For the ITM we newly implemented the relevant pieces, based on the IDM. We validated our numerical calculations by comparing with the earlier works in the SM [7,9] as well as in the IDM [19], while the results in the ITM and the THDMs are reported for the first time in this article.…”
Section: Two Higgs Doublet Modelsmentioning
confidence: 61%
“…We briefly review the total cross section for e + e − → hγ in the SM [6][7][8][9]. As mentioned in Sec.…”
Section: Process Of E + E − → Hγ In the Smmentioning
confidence: 99%
See 2 more Smart Citations
“…The next-to-leading order QCD corrections to the production of a Higgs boson associated with a photon has been calculated in Ref. [61], where it has been shown that these corrections could increase the production rate up to 20%. Within the simplified model, the e − e + → h 2 γ process proceeds through loop-level Feynman diagrams which include SM fermions and gauge bosons as well as the additional contributions from the vector like top quark.…”
Section: Singlet Scalar Production In Association With a Photonmentioning
confidence: 99%